If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7 + -12) = m + -6 Combine like terms: 7 + -12 = -5 4(-5) = m + -6 Multiply 4 * -5 -20 = m + -6 Reorder the terms: -20 = -6 + m Solving -20 = -6 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -20 + -1m = -6 + m + -1m Combine like terms: m + -1m = 0 -20 + -1m = -6 + 0 -20 + -1m = -6 Add '20' to each side of the equation. -20 + 20 + -1m = -6 + 20 Combine like terms: -20 + 20 = 0 0 + -1m = -6 + 20 -1m = -6 + 20 Combine like terms: -6 + 20 = 14 -1m = 14 Divide each side by '-1'. m = -14 Simplifying m = -14
| 2.7x+64=7.29+8x | | x*8/x^2 | | 10z+2=3x-2z | | 84-3x=10x-19 | | j+74=158 | | 9x+17=17+9x | | 180-7x=38x-20 | | x^2/8=x | | -x+3z=19 | | 8x+5=15+6x | | 6/7x-9/7=6 | | 3x^2-8x-32=0 | | 3x+y-2z=-8 | | x^3=5x^2 | | 5x+5=15+6x | | 1.005=0.005+0.95 | | 10X-2+5X=15X-2 | | 2n=317 | | 2/7x=2+3x | | 2x^3+40x=18x^2 | | 9X-27+6=-5+4X-3X | | 127=36+y | | (x-8)(x+3)=1-5x | | 20+t=66 | | 18x^3-63x^2+9x= | | 0=2x^2+22x+48 | | 1/9+1/9+1/9 | | x-5=2y-5 | | 1/3(6x-9)-10 | | 2+(x-4)+8=3x-8 | | 3x+35=5x-15 | | 2x^2-24x+70=0 |